An Interval-Valued Trapezoidal Intuitionistic Fuzzy TOPSIS Approach for Decision-Making Problems - Mallika, Ch; Sireesha, V. (SN computer science, 2023)
The Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) is a well-known multi-criteria decision-making strategy that has been widely used in research decision-making problems. Furthermore, interval-valued trapezoidal intuitionistic fuzzy sets (IVTrIFSs) have a consecutive domain, which allows for efficient uncertainty management. Hence, an IVTrIF TOPSIS method is proposed in this study. TOPSIS is a method for selecting and comparing alternatives based on similarity/distance measurements. Hence, a new ranking method based on the Dice similarity metric was developed and the properties of the similarity measure were validated. Further, the problem of selecting the best business venture is solved using the suggested approach. The best alternative is found. The results are compared to those of previous technique IVTrIF combinative distance-based assessment method. From the result analysis, it is noticed that the proposed method can be used as an alternative to solve decision-making problems in IVTrIF contexts.